2001
DOI: 10.1128/aac.45.11.3205-3208.2001
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Erythromycin Resistance among Clinical Isolates of Streptococcus agalactiae in Taiwan

Abstract: The in vitro susceptibilities of 266 isolates of Streptococcus agalactiae determined by the agar dilution method showed that 6% of isolates were nonsusceptible to penicillin and 46% was resistant to erythromycin. Of the erythromycin-resistant isolates, 86.3% had the macrolide-lincosamide-streptogramin (MLS) resistance phenotype (constitutive MLS, 85.5%; inducible MLS, 0.8%) and 13.7% had the M phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
67
3
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 30 publications
22
67
3
2
Order By: Relevance
“…In the years 1999 to 2002, more than half of the isolates were penicillin nonsusceptible and one-quarter of the isolates were fully penicillin resistant and multiresistant. These rates are comparable to those obtained in studies in other Asian countries, including South Korea (2,13,16,19,29,30,31,32), Hong Kong (10,11,12,18), Taiwan (7,8,9,27), Singapore (15,28,30), Thailand (30), and Japan (30,36), but are considerably higher than those obtained in studies in other countries in this region such as China (21,35), Malaysia (25), and the Philippines (1). In a recent multicenter study of 996 clinical isolates from 11 Asian countries, including 176 isolates from blood or CSF, 18.3% showed intermediate susceptibility and 22.7% were fully resistant (30).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the years 1999 to 2002, more than half of the isolates were penicillin nonsusceptible and one-quarter of the isolates were fully penicillin resistant and multiresistant. These rates are comparable to those obtained in studies in other Asian countries, including South Korea (2,13,16,19,29,30,31,32), Hong Kong (10,11,12,18), Taiwan (7,8,9,27), Singapore (15,28,30), Thailand (30), and Japan (30,36), but are considerably higher than those obtained in studies in other countries in this region such as China (21,35), Malaysia (25), and the Philippines (1). In a recent multicenter study of 996 clinical isolates from 11 Asian countries, including 176 isolates from blood or CSF, 18.3% showed intermediate susceptibility and 22.7% were fully resistant (30).…”
Section: Discussionsupporting
confidence: 61%
“…The Vietnamese Spain 23F -1 pneumococci were all erythromycin resistant but tetracycline susceptible. This is not typical of the clone in Spain (20) but is a common feature of the Spain 23F -1 pneumococci in Asia (8,9,11,16,27). Two of the penicillin-resistant 19F isolates from the nasal carriage study were found to be the Spain 23F -1 clone by MLST.…”
Section: Discussionmentioning
confidence: 99%
“…This increase may be related to the increased use of macrolides in the hospital. A higher prevalence of erythromycin resistance has been reported in other studies, namely from Korea (20 %) (Uh et al, 2001), Brazil (53 %) (Betriu et al, 2003) and Taiwan (46 %) (Hsueh et al, 2001). Most of the erythromycin-resistant GBS isolated in our study (Table 3) contained ermB or ermTR.…”
Section: B-lactammentioning
confidence: 46%
“…Este comportamiento sigmoidal de la resistencia es muy similar al observado en los países con alta resistencia a la penicilina (33). Para el año 2004, el 37,7% de los aislamientos presentaron resistencia a la penicilina, muy inferior a la informada para los países asiáticos (11), pero superior a la de la mayoría de los países europeos (33); este mismo comportamiento se observó con la resistencia a SXT (34). Estas diferencias en los niveles de resistencia reflejan la importancia de la presión selectiva de los antibióticos en la selección de fenotipos resistentes como consecuencia directa del consumo de antibióticos, la cual difiere ampliamente entre los países europeos, que tienen un programa de control de medicamentos (33), y países como el nuestro donde no se cuenta con políticas para el buen uso de los antimicrobianos.…”
Section: Discussionunclassified